Preparing hospitals for bioterror : a medical and biomedical systems approach - McIsaac, Joseph H. (Biomedical Engineering., 2006)
Hospital Preparation for Bioterror provides an extremely timely guide to improving the readiness of hospitals or healthcare organizations to manage mass casualties as a result of bioterrorism, biological warfare, and natural disasters. Contributions from leading law enforcement agencies, hospital administrators, clinical engineers, surgeons and terror-prevention professionals provide the most comprehensive, well-rounded source for this valuable information. Chapters on logistics and protecting the infrastructure help personnel distinguish the specific risks and vulnerabilities of each unique institution and assists in identifying specific solutions for disaster and bioterrorism preparedness. Principles and techniques discussed are applicable to all disasters, both large and small, not just bioterrorism Technical aspects such as hospital power and telecommunications are covered, in addition to patient care, response to mass casualties, large-scale drills, and surge capacity. Organized along functional lines, patient flow, medical specialty, and infrastructure A complimentary website with supplementary materials, check-lists, and references enhances the text and provides additional resources for preparedness.